Serum receptor activator of nuclear factor κB ligand (RANKL) levels predict biochemical recurrence in patients undergoing radical prostatectomy - Todenhöfer, Tilman; Hennenlotter, Jörg; Leidenberger, Philipp; Wald, Alexander; Hohneder, Andrea; Kühs, Ursula; Mischinger, Johannes; Aufderklamm, Stefan; Gakis, Georgios; Blumenstock, Gunnar; Stenzl, Arnulf; Schwentner, Christian (BJU international, 2014)
What's known on the subject? and What does the study add? There is increasing evidence that the receptor activator of nuclear factor κB ligand (RANKL) pathway not only contributes to the development of bone metastases, but also influences tumour biology in earlier stages of cancer. The study shows that preoperative serum levels of RANKL and its inhibitor osteoprotegerin (OPG) have a prognostic impact in patients undergoing radical prostatectomy for clinically localized prostate cancer. Both high levels of RANKL and a higher RANKL/OPG ratio are independent predictors of early biochemical recurrence in these patients. Objective To assess the prognostic impact of proteins of the receptor activator of nuclear factor κB (RANKL) pathway in serum samples from patients undergoing radical prostatectomy. Patients and Methods We retrospectively determined soluble RANKL (sRANKL) and osteoprotegerin (OPG) by ELISA in serum samples of 178 patients undergoing radical prostatectomy between 2004 and 2006. Clinical and patient follow‐up data were analysed using the Wilcoxon–Mann–Whitney test, the Kaplan–Maier method, and single variable or multifactorial Cox proportional hazards analysis. Results Higher serum sRANKL levels (P = 0.01), lower serum OPG levels (P = 0.01) and a higher sRANKL/OPG ratio (P = 0.004) were significant risk factors for biochemical recurrence (BCR). In multifactorial analysis, adjusted for the common risk factors for BCR, sRANKL and sRANKL/OPG ratio were confirmed as independent prognostic factors. Neither sRANKL nor OPG showed a clear association with histopathological factors such as pT stage, pN Gleason score or resection margin status, nor were they associated with prostate‐specific antigen level. Conclusions Greater activity of the RANKL pathway in the serum of patients with prostate cancer undergoing radical prostatectomy is a risk factor for BCR. The RANKL pathway seems to contribute to the biological behaviour of prostate cancer even at the organ‐confined stage of the disease.